Understanding Pragmatics as a Way to Practice Natural Communication Skills in Various Contexts of Interactions - Leffi Noviyenti; Khairul Anwar (STAI Hubbulwathan Duri, 2023)
Students’ problems in using English to communicate need to be handled seriously. Teaching English is no more teaching the knowledge of English only but also the use of context. This library research elaborates on the importance of pragmatics for EFL students to improve their communication skills in various contexts of interaction and to strengthen the importance of pragmatic competence for non-native English teachers in teaching natural English communication. Documentation is the collecting technique using a checklist and fieldnote instruments. The primary sources are theories about pragmatics and teaching communication from books and published journals. In order to obtain correct and precise results in analyzing data, a content analysis technique is used. The data analysis procedure covers determining the design, which is linkage analysis, finding main data, and theories about pragmatics from books, then finding contextual knowledge from published research related to pragmatics and teaching English communication, and finally, writing and interpreting the linkage to describe the results. The findings show that pragmatics should not limitedly act as classroom instructions but as competence to be constantly developed and practised for students or teachers. Pragmatics should be seen from its whole aspect in order to communicate naturally and contextually. It can also be concluded that opportunities for pragmatic practice should be provided to achieve the goal of teaching English, that is, the ability to use English in various contexts of interaction.